ANALISIS DAN PERANCANGAN ARSITEKTUR TEKNOLOGI INFORMASI BERBASIS CLOUD COMPUTING UNTUK INSTITUSI PERGURUAN TINGGI DI SUMATERA SELATAN - Edi Surya Negara (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
Information technology architecture based cloud computing become one of the architectural model of the development of information technology for the college. Based on data from the Department of Education of South Sumatra, is currently in South Sumatra there are 100 public and private universities. Analysis and design of information technology architecture based cloud computing will be applicable to all universities in South Sumatra, to standardize the development of information technology at each university. So with the standardized architecture teknlogi this information will have a significant impact in improving the quality of higher education in South Sumatra Indonesian people to realize intelligent and competitive. Analysis and design will use the TOGAF Architecture Development Method methods adapted to the concept of cloud computing. The first stage of the analysis process is done by gathering data from each university in South Sumatra with a survey and observation. This study tour resulting in the architecture of cloud based applications and information technology architecture based on cloud computing that can be implemented in higher education institutions in South Sumatera